Analysis of shot success indicators among female basketball players - Stankovic, D.; Kocic, M.; Milenkovic, S.; Bubanj, S. (23rd International Scientific Conference "FIS COMMUNICATION 2021", 2021)
More complex methods in the indicators of success analysis in the game bring a larger number of data whose systematization and analysis is a necessary prerequisite for a successful team scouting. Thus, conditions are created for gaining an advantage in terms of adequate technical and tactical preparation of opposing teams. The aim of the research is to analyze the indicators of shot success in the most efficient basketball players and determine the difference between them. A total of 2838 shot indicators were analyzed with the use of non-parametric and parametric statistics. The type of movement before the shot, the type of shot, the period of the game when shooting, the distance from which the shot is performed and the outcome of the shot were analyzed. Chi-square test and ANOVA method was used for determining the differences in shot success indicators between top ten female basketball players. Also, the post hoc and z-test analysis for comparing the differences among specific pairs of players were conducted. With the use of Chi-square test and ANOVA method, the results showed statistically significant differences among the players with the p-level of (p.0.05). The players differentiated in the type of movement before the shot (p=0.00), the type of shot (p=0.00), the period of the game when shooting (p=0.01), the distance from which the shot is performed (p=0.00), except in the outcome of the shot (p=0.29). It was found that the players statistically differed in all shot variables except in the shot outcome variable. In variables where statistical difference was found, post hoc and z-tests showed that players who played on center and power forward positions mainly differed from players on guard positions in most of the indicators.